The Effect of Job Insecurity and Job Promotion on Performance Mediated by Job Satisfaction in BRI Outsourcing Employees Medan Regional Office - M Nur Kuncoro; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This research aims to find the effect of job insecurity and position promotion on performance which is mediated by job satisfaction in BRI Outsourcing Employees at the Medan Regional Office. The type of research used in this research is descriptive research with a quantitative approach. In this research, the sample studied was the Back Office section. totaling 54 people, the back office section was taken because what was assessed using the KPI was the back office section, then the sampling technique used was saturated sampling where the entire population of 54 was sampled. The data analysis technique used in this research was path analysis using the PLS SEM tool, The results of this research are: In this research, Job Insecurity influences performance and is mediated by Job Satisfaction in BRI outsourcing employees, Medan Regional Office. This can be seen from the original sample value, namely 0.395 and the p value of 0.001, meaning that in this study the hypothesis is accepted, meaning Job Satisfaction. mediates the relationship between Job Insecurity and Performance because the p value is 0.001 < 0.05. In this study, Job Promotion has no effect on Performance which is mediated by Job Satisfaction for BRI outsourced employees at the Medan Regional Office. This can be seen from the original sample value of 0.034 and the p value of 0.621 This means that in this study the hypothesis is rejected. Job satisfaction mediates the relationship between position promotion and performance because the p value is 0.621 > 0.05